Ketersediaan Tenaga Kesehatan Promotif dan Preventif Puskesmas di Kabupaten Jember - Rizkiy Shofiah; Dewi Prihatini; Sebastiana Viphindartin (Multidisciplinary Journal, 2019)
Community Health service is the first level facility which enables promotive and preventive service to gain health. The administration of health service should be supported by qualified medical workers to support the function of community health service. Concerrning its function, the service is required to have at least five promotive and preventive workers including laboratory analyst, nutritionist, public health workers, and sanitary worker. The availability of medical human resources in Community Health service has not yet distributed evenly in Jember Regency. The recruitment of the health human resources in Jember still focuses on medical workers This research is a descriptive research using qualitative approach aiming at describing the availability of promotive and preventive workers in Community health service in Jember regency based on Minimum Resources Standard. The findings shows that out of 50 Health service 30 of them do not have analyst , 28 without nutritionist, 37 with no public health workers and 36 without sanitation workers , as shown by data from Health Office. The informant reveals that the uneven distribution of promotive and primitive workers is caused by (1) Health office zero recruitment for Health service, (2) the policy restriction for health service for utrititonist, (3) the limit of Health service budget for the recruitment. Keyword: the availability, promotive and preventive workers, community health service